PENGARUH CITRA MEREK, KUALITAS PRODUK DAN E-WOM TERHADAP MINAT BELI PRODUK RAMAH LINGKUNGAN - Cantika Widi Pramesti; Anton Agus Setyawan (Jurnal Bina Bangsa Ekonomika, 2024)
The purpose of this study is used to analyze whether brand image, product quality and E-WOM can influence consumer buying interest in environmentally friendly products at FEB UMS. This research method is quantitative, with non-probability sampling techniques  with purposive sampling methods. This research data is primary data. The population of this study is FEB students of Muhammadiyah University of Surakarta. The sample in this study was 100 respondents. Data collection methods are used by researchers using online questionnaires with the help of Google Form facilities. The data analysis method in this study uses Partial Least Square (PLS) Analysis. Data analysis in this study used the help of Smart PLS application software. The results in this study show that brand image has a positive and significant influence on buying interest. Product quality has a positive and significant influence on buying interest. E-WOM also has a positive and significant influence on buying interest